A contingent diffusion model of local climate change policy adoption: Evidence from Southern California cities. (January 2022) - An, Brian Y.; Butz, Adam M.; Mitchell, Joshua L.
Abstract: Climate change policy is an essential driver of urban sustainability, yet minimal research has examined how they emerge and spread across cities in shared metropolitan areas. While policy diffusion or policy mobility theories could explain the aforesaid, much of the international scholarship have not utilized an amalgamation of these two complementary theoretical perspectives. As a result, we lack a comprehensive understanding of the regional dynamics and spillover effects local governments can generate for urban sustainability. This article proposes a contingent diffusion model to examine the intra-regional adoption of local climate action plans within Southern California from 2000 to 2018. We find that neighboring jurisdictions that adopt climate policy increase the likelihood of a home city's adoption. Yet, neighboring effect is contingent on the home city's existing pro-environmental policy propensity. However, in contrast to conventional wisdom, this study finds no evidence that local environmental advocacy groups play a crucial role in the diffusion of municipal climate initiatives. Altogether, the results suggest that a regional diffusion model of policy innovations is more likely successful when adaptive capacity is in place to facilitate green infrastructure. These findings provide implications for policymakers and planners who want to achieve successful spillovers of urban climate policies across local governments. Highlights: 49 cities among 190 cities within the Southern California Region adopted climate action plans (CAPs) from 2000 to 2018. Local governments can be incubators and transmitters of climate policy innovations to others within a shared regional space. This study builds on policy diffusion and mobility literature to examine an intra-regional diffusion of local climate policy. A neighboring spillover effect is found to be contingent on a home city's existing pro-environmental adaptive capacity. To tap such spillover effects, urban and regional planners must consider their cities' adaptive capacity or lack thereof.